2018
DOI: 10.1172/jci122819
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor splice variant-7 expression emerges with castration resistance in prostate cancer

Abstract: BACKGROUND. Liquid biopsies have demonstrated that the constitutively active androgen receptor splice variant-7 (AR-V7) associates with reduced response and overall survival from endocrine therapies in castration-resistant prostate cancer (CRPC). However, these studies provide little information pertaining to AR-V7 expression in prostate cancer (PC) tissue.METHODS. Following generation and validation of a potentially novel AR-V7 antibody for IHC, AR-V7 protein expression was determined for 358 primary prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
311
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(337 citation statements)
references
References 91 publications
17
311
0
Order By: Relevance
“…Interestingly, Qu et al [15] performed a comparable IHC approach as performed in this study and noted at the stage of CRPC a much higher rate with 58.7% AR-V7 positivity [18]. This observation is in line with the findings of Sharp et al [31] who showed an AR-V7 detection rate of 75% by using the AR-V7 antibody clone EPR15656 [18]. The high AR-V7 detection rate in our study could also be caused by multiple pre-treatment at the stage of CRPC and overall insufficient performance status at a high tumour burden [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, Qu et al [15] performed a comparable IHC approach as performed in this study and noted at the stage of CRPC a much higher rate with 58.7% AR-V7 positivity [18]. This observation is in line with the findings of Sharp et al [31] who showed an AR-V7 detection rate of 75% by using the AR-V7 antibody clone EPR15656 [18]. The high AR-V7 detection rate in our study could also be caused by multiple pre-treatment at the stage of CRPC and overall insufficient performance status at a high tumour burden [18].…”
Section: Discussionsupporting
confidence: 89%
“…The high AR-V7 detection rate in our study could also be caused by multiple pre-treatment at the stage of CRPC and overall insufficient performance status at a high tumour burden [18]. However, a limitation of the predictive value of AR-V7 in our study could be based on small cohort size (n = 26) and possible widely reported cross-reaction of AR-V7 antibodies [18,23,[31][32][33].…”
Section: Discussionmentioning
confidence: 75%
“…Finally, this study showed an increase of ARv7 in metastatic PRCA, as expected . Interestingly, we detected ARv7 positivity at every stage of PRCA progression, in contrast to others . This inconsistency could be due to different reagents and/or analysis techniques.…”
Section: Discussionsupporting
confidence: 61%
“…28 Interestingly, we detected ARv7 positivity at every stage of PRCA progression, in contrast to others. 27 This inconsistency could be due to different reagents and/or analysis techniques. Though low in abundance at earlier stages of PRCA progression, these ARv7-positive cells may represent a cell population that contributes to disease recurrence.…”
Section: Ar and Arv7 Coexpression Predicts Advanced Gs And Disease mentioning
confidence: 99%
“…Furthermore, several AR splice variants (AR-V1, -V7, and -V9) lacking LBD are also commonly reported ( Figure 2). Another splice variant, AR-V567es is also reported in prostate tumor [34][35][36][37]. Studies have documented that even though some AR variants lack LBD, they retain their ability to bind to DNA and promote constitutive gene transcription in the absence of androgens [38,39].…”
Section: Androgen Receptor: Structure and Mechanisms Of Actionmentioning
confidence: 99%